Correlates of uptake of HIV testing among children and young adolescents in Akwa-Ibom state, Nigeria: a secondary data analysis of the Akwa-Ibom aids indicator survey, 2017 - Damilola Adetoro; Hadiza Khamofu; Titilope Badru; John Markson; Oluwasanmi Adedokun; Nana Sandah-Abubakar; Ibrahim Dafa; Mario Chen; Robert Chiegil; Kwasi Torpey (BMC, 2021)
Abstract Background In order to end the AIDS epidemic by 2030, there is a need to significantly reduce the rate of new infection among children and young adolescents. Identifying the correlates of testing behaviour is necessary to improve HIV testing campaigns by refining messages that target individuals in this age group. The objective of this study was to determine the correlates of HIV testing among children and young adolescents in Akwa-Ibom, Nigeria. Methods The outcome was a secondary data analysis of the 2017 Akwa-Ibom AIDS Indicator Survey. Data of 4037 children and young adolescents aged 0-14 years was assessed in this study. Analysis was done using STATA version 16. Chi-squared test and logistic regression models were used to measure association and its strength between uptake of HIV testing and some independent variables (child/caregiver's age, sex, educational status, child's location, caregiver's knowledge of HIV and caregiver ever tested for HIV) at 5% significance level. Results Result showed that only 14.2% of the children and young adolescents have been tested for HIV. Previous history of blood transfusion (AOR = 5.33, 95%C.I = 2.60-10.92, P = < 0.001), caregiver's level of education (AOR = 2.67, 95%C.I = 1.30-5.51, P = 0.008) and caregiver ever tested for HIV (AOR = 8.31, 95%C.I = 5.67-12.19, P = < 0.001) were significantly associated with uptake of HIV testing. Conclusion This study concludes that a large proportion of children and young adolescents in Akwa-Ibom state have never been tested for HIV. There is a need for HIV testing interventions to be targeted towards this age groups and their parents/guardian. Addressing the knowledge gap amongst caregivers especially in rural areas is crucial towards improving the effectiveness of HIV testing interventions.